2021
DOI: 10.3390/cancers13194763
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase (HDAC)-1, -2, -4, and -6 in Uveal Melanomas: Associations with Clinicopathological Parameters and Patients’ Survival

Abstract: Background: Uveal melanoma (UM) represents the most common primary intraocular malignancy in adults, exerting high metastatic potential and poor prognosis. Histone deacetylases (HDACs) play a key role in carcinogenesis, and HDAC inhibitors (HDACIs) are currently being explored as anti-cancer agents in clinical settings. The aim of this study was to evaluate the clinical significance of HDAC−1, −2, −4, and −6 expression in UM. Methods: HDAC−1, −2, −4, and −6 expression was examined immunohistochemically in 75 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…Mechanistically, tubulin acetylation stabilizes the level of the anti-apoptotic protein Mcl-1 by protecting it from degradation [69]. In line with these studies, aberrant expression of tubulin deacetylase HDAC6 has been reported in several cancer cell lines and tumor models [70,71]. In addition, upregulation of HDAC6 increases cell motility in breast cancer cells, thus contributing to cancer metastasis [72], whereas in glioblastoma cells genetic silencing of HDAC6 decreases cellular malignancy and reverses the mesenchymal phenotype [73,74].…”
Section: The Tubulin Code and Its Associated Enzymes In Cancermentioning
confidence: 81%
“…Mechanistically, tubulin acetylation stabilizes the level of the anti-apoptotic protein Mcl-1 by protecting it from degradation [69]. In line with these studies, aberrant expression of tubulin deacetylase HDAC6 has been reported in several cancer cell lines and tumor models [70,71]. In addition, upregulation of HDAC6 increases cell motility in breast cancer cells, thus contributing to cancer metastasis [72], whereas in glioblastoma cells genetic silencing of HDAC6 decreases cellular malignancy and reverses the mesenchymal phenotype [73,74].…”
Section: The Tubulin Code and Its Associated Enzymes In Cancermentioning
confidence: 81%
“…In line with previous studies, which confirmed HDAC gene [ 243 , 244 ] and protein [ 245 ] expression in UM, the authors evaluated HDAC-1, HDAC-2, HDAC-4 and HDAC-6 through IHC and aimed to determine their role as prognostic factors [ 193 ]. HDAC-1 and HDAC-2 had both nuclear and cytoplasmic expression, whereas HDAC-4 and HDAC-6 were mostly expressed in the cytoplasm of UM cells [ 193 ]. Among the four studied HDACs isoforms, HDAC-2 was the most frequently expressed, with a more significant nuclear expression pattern, and the expression of HDAC-2 the only proven to be an independent factor of better survival in UM [ 193 ].…”
Section: Immunohistochemistry-based Novel Prognostic Biomarkers In Uveal Melanomamentioning
confidence: 96%
“…Consequently, HDAC inhibitors have constituted promising anti-neurodegeneration and anti-cancer therapies [ 241 , 242 ]. The prognostic significance of HDAC expression in UM was recently evaluated in a study involving 75 UM cases [ 193 ]. In line with previous studies, which confirmed HDAC gene [ 243 , 244 ] and protein [ 245 ] expression in UM, the authors evaluated HDAC-1, HDAC-2, HDAC-4 and HDAC-6 through IHC and aimed to determine their role as prognostic factors [ 193 ].…”
Section: Immunohistochemistry-based Novel Prognostic Biomarkers In Uveal Melanomamentioning
confidence: 99%
See 2 more Smart Citations